Review on synthesis of porous TiO2-based catalysts for energy conversion systems. Issue 18 (15th September 2021) - Mao, Hui; Zhang, Fangfang; Du, Meng; Dai, Longjun; Qian, Yongteng; Pang, Huan
Abstract: Porous TiO2 -based catalysts have recently received remarkable attention in the field of energy conversion systems, including hydrogen/oxygen evolution reaction, oxygen/nitrogen reduction reaction, and photodegradation of pollutants owing to their unique structure, large surface area, and good chemical stability. In this report, we review existing research on porous TiO2 -based catalysts for energy conversion systems during the past four years. First, the advantages of porous TiO2 -based catalysts are introduced. Next, the synthetic approaches in developing porous TiO2 -based catalysts are summarized. The different types of energy conversion systems based on porous TiO2 -based catalysts are then presented. Finally, the challenges and future perspectives in synthesizing porous TiO2 -based catalysts are discussed.